Comparative study of fascia iliaca block vs. pericapsular nerve group block in preoperative pain management for fragility hip fractures - Acharya , Krishna Prasad; Yadav, Rupesh Kumar; Hamal, Pawan Kumar; Pokhrel, Nabin; Sherpa, Tshering; Maharjan, Surendra; Tamang, Jeevan; K.C., Ribesh; Yadav, Deepak Kumar; Kafle, Neetish; Nepali, Gyanendra; Pandey, Dipendra (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Hip fractures in elderly patients are associated with significant morbidity and require effective preoperative pain management. This study compares the efficacy of the Fascia Iliaca Block (FIB) and the Pericapsular Nerve Group (PENG) block for preoperative analgesia in patients with fragility hip fractures. Methods: A prospective observational study was conducted at the National Trauma Center in Nepal, involving 72 patients aged 60 years or older with hip fractures. Patients received either an FIB or PENG block using 20 ml of 0.25% ropivacaine under ultrasound guidance. Pain scores (VAS) were recorded at baseline, 15 min, 2 hr, 4 hr, 6 hr, and 12 hr post-block.Results: The PENG group demonstrated consistently lower VAS scores at all time points. Motor block and complications were also lower in the PENG group. The duration of block performance was slightly longer in the PENG group.Conclusion: The PENG block provided superior analgesia with fewer complications compared to FIB and may be a preferred option for preoperative pain management in elderly hip fracture patients.